The Effect of Competence and Self-Efficacy on Performance Moderated by Transformational Leadership : A Study of The Regional Secretariat of Batang Regency - Muhammad Fathur Rahman; Tristiana Rijanti (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to examine and analyze the influence of competence and self-efficacy on employee performance, with transformational leadership acting as a moderator, in the Regional Secretariat of Batang Regency. Data collection was conducted by distributing questionnaires to 109 respondents, selected from a total population of 189 employees. The data analysis was performed using SPSS version 27, employing descriptive statistical tests, validity tests, reliability tests, and regression analysis to determine the relationships between the variables. The results of the study revealed several key findings. First, competence was found to have a negative and significant effect on employee performance. This suggests that higher levels of competence do not necessarily lead to improved performance, possibly due to other factors, such as organizational culture or work environment, that may counterbalance the effects of individual competence. Second, self-efficacy was found to have a positive and significant effect on employee performance. This indicates that employees who believe in their ability to perform tasks are more likely to achieve better results. Moreover, transformational leadership was found to strengthen the effect of competence on employee performance. This suggests that leaders who inspire and motivate their employees, encourage innovation, and provide a supportive work environment can enhance the positive impact of competence on performance. However, transformational leadership was also found to weaken the effect of self-efficacy on employee performance. This could be due to the fact that transformational leadership provides external motivation and guidance, which may reduce the reliance on employees' self-confidence in achieving performance goals. In conclusion, the study highlights the complex relationships between competence, self-efficacy, and performance, with transformational leadership playing a significant moderating role in these dynamics. The findings provide valuable insights for organizations seeking to enhance employee performance through leadership strategies.